INFLUENCE OF INDIVIDUAL CHARACTERISTICS, BEHAVIOR AND NOISE INTENSITY ON BLOOD PRESSURE IN PONOROGO PLASTIC INDUSTRY'S WORKERS: Pengaruh Karakateristik Individu, Perilaku dan Intensitas Kebisingan Terhadap Tekanan Darah pada Pekerja Industri Plastik Ponorogo - Ari Rahmawati Putri; Aini Fadlila; Soedjajadi Keman; Saliza Binti Mohd Elias (Universitas Airlangga, 2023)
Background: Noise is an unwanted sound that can be caused by any human activity. Continuous use of machines that produce noise in the work environment will have a negative impact on workers, for example is increasing blood pressure. Purpose: This study aimed to analyze the influence of individual characteristics, behavior and noise intensity on increasing blood pressure in workers in the Ponorogo's plastic industry. Methods: The study used prospective cohort design. The sample of the study was 32 respondents who received continuous noise exposure from injection machine for 8 hours/ day. The variables include individual characteristics, behavior, noise intensity, and increased blood pressure. The data were analyzed using SPSS with paired sample t-test and multiple linear regression. Results: The result showed that the average increase in systolic and diastolic blood pressure before and after working is 5.75 mmHg and 5.31 mmHg. If analyzed by statistical paired t-test, the significance value of p = 0.00 < α = 0.05 is obtained. Furthermore, multiple linear regression test is used for variables of individual characteristics, behavior and noise intensity on increasing blood pressure showing a significance value of 0.00 <0.05 and F count (6.79 and 6.32) > F table (2.49). Conclusion: Individual characteristics, behavior and noise intensity have an effect on increasing blood pressure in workers in the Ponorogo's plastic industry. Medical checkup and ear protection equipment are needed for workers.